Application of computer image processing technology in Web Design - Ma, Yue; Guangrong, Dan (2020 2nd International Conference on Information Technology and Computer Application (ITCA), 2020)
Computer image processing technology is an important part of web design, which can effectively improve the appeal and artistic sense of web page. With the development of the times, the influence of the network in people's life is more and more big, web design has also been widely concerned by people. The application of computer image processing technology in web page design can make the web page more beautiful and efficient. With the continuous improvement of the current society's attention to network publicity, it provides favorable conditions for the combination of art and network development. The application of computer image processing in web design can increase the artistry and attractiveness of web pages, and achieve the purpose of network publicity through the stimulation of people's interest, which can greatly promote the development of the industry. This paper analyzes the web design image processing knowledge and computer image processing technology in the application of web design, for reference only.